If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y/12=-5
We move all terms to the left:
y/12-(-5)=0
We add all the numbers together, and all the variables
y/12+5=0
We multiply all the terms by the denominator
y+5*12=0
We add all the numbers together, and all the variables
y+60=0
We move all terms containing y to the left, all other terms to the right
y=-60
| 4x+90=11 | | 16z-7z=9 | | 9/10-1/x=4/5 | | -7=-3+f | | 8x^2-2=24 | | 3v-2v-v+v=14 | | 1/3(6-9x)=6x+11 | | 31=3(x-3)-8x | | 15k-5k-6k=12 | | 4(p–7)= | | 4y-7=-2y+11 | | 15k−5k−6k=12 | | 15j-9j-j+j-3j=18 | | 5x-13=7x+8 | | x^2-11.25x=1/45 | | –6+2k=k | | 6r+3=4r+11 | | −14=x−12 | | .65x=500 | | –9+5m=8m | | (x/2)+(1/2)=44 | | x+3.17=12.08 | | 5+3x+1x=21 | | q+6=-12 | | 0.05(4x)=16.2 | | r2+14r=39 | | 85+5x=20 | | -8(t-100)=8 | | 23-3x=40 | | -3(6x-2)+5=-18x+11 | | 22+6z=88 | | n/6+65=72 |